Analisis Pendapatan Petani Kopi Arabika Dan Faktor-Faktor Yang Mempengaruhinya Di Desa Tanjung Beringin Kecamatan Sumbul Kabupaten Dairi - Saragi, Frans Seda; Simanullang, Endang Sari (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
Aims to analyze the income of Arabica coffee farmers in Tanjung Beringin Village, Sumbul District, Dairi Regency.To analyze the factors that affect the income of Arabica coffee farmers in Tanjung Beringin Village, Sumbul District, Dairi Regency. This research uses a quantitative method, namely a method that uses numbers to solve problems based on existing data in the field to conclude. The sampling of coffee farmers in this study used the Slovin formula. Where the population is 60 farmers and the sample in this study was 30 coffee farmers. The research results show that the production factors that significantly influence the income of coffee farmers in Tanjung Beringin Village are land area, seeds, and labor. The income received by coffee farmers in Tanjung Beringin Village, Sumbul District, Dairi Regency is Rp. 16. 816.853 /Farmer.